Supervisi Pendidikan Dalam Lingkup Pendidikan Islam Era Kontemporer - Muhammad Syafi’i; Darul Hikmi; Siti Patimah; Andi Warisno; Nurul Hidayati; A. Gani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Islamic education in the contemporary era faces complex challenges such as technological advancement, globalization, and cultural shifts; therefore, educational supervision becomes a crucial instrument to ensure the quality of holistic learning. This study aims to examine the concepts, objectives, functions, and implementation of Islamic educational supervision in a modern context, with a focus on teacher development and the strengthening of students’ moral, ethical, and spiritual values. Using a qualitative approach through the library research method, data were collected from academic literature, including books, journals, and scientific documents related to Islamic educational administration. The findings indicate that Islamic educational supervision goes beyond administrative monitoring, encompassing the development of teacher professionalism, the enhancement of innovative teaching methods, and the reinforcement of religious and character dimensions. In the contemporary era, supervision must be adaptive and responsive, covering curriculum, student affairs, personnel, facilities and infrastructure, finance, public relations, and administration, in order to produce a generation that is knowledgeable, faithful, well-mannered, and prepared to face global challenges. In conclusion, Islamic educational supervision serves as a strategic means of transforming values and professionalism, ensuring the relevance of Islamic education in response to the demands of the times.